The effects of masculine honor beliefs and beliefs in mental health stigma on honoring and supporting physical versus psychological injury in the military - Schiffer, Ashley (Kansas State University, 2023)
Many members of the military suffer injury as a result of their service, physically and/or psychologically, but these injuries are stigmatized differently (Goffman, 1963). Individual differences in Masculine Honor Beliefs (MHB; i.e., beliefs about men’s values and behaviors, specifically that aggression is sometimes justifiable; Saucier et al., 2016) and in beliefs about mental health stigma likely affect perceptions of these different military injuries. For instance, although MHB are likely prevalent in the military, given its culture of honor (Saucier & McManus, 2014), individuals higher in MHB are less likely to believe combat contributes to PTSD and tend to discourage public discussion of mental health (Lawless et al., in preparation). In fact, the values of toughness and self-sufficiency that are promoted in both the military and honor cultures can contribute to increased beliefs in mental health stigma (e.g., Hoge et al., 2006). This research will assess how MHB and beliefs in mental health stigma (as assessed by the Endorsed and Anticipated Stigma Inventory; EASI; Vogt et al., 2014) relate to perceptions of how deserving each type of injury is in terms of military honors (Study 1) and monetary allocations between two veterans organizations (Study 2). Specifically, Study 1 will explore support for recognizing PTSD in Purple Heart qualifications, a military honor traditionally reserved for physical injuries. In Study 2, participants will allocate $1,000 between two veterans organizations: one that supports veterans with physical injuries and one that supports veterans with psychological injuries. This program of research has great theoretical implications for the nature of MHB in perceptions of military mental health as well as practical implications in terms of who supports the military’s recognition of psychological injuries in military honors and how they allocate money toward helping veterans with these injuries.
Keywords: masculine honor beliefs; mental health stigma; military; injury